Authigenic and Detrital Carbonate Nd Isotope Records Reflect Pulses of Detrital Material Input to the Labrador Sea During the Heinrich Stadials. Issue 2 (28th January 2023) - Filippova, Alexandra; Frank, Martin; Kienast, Markus; Gutjahr, Marcus; Hathorne, Ed C.; Hillaire‐Marcel, Claude
Abstract: Limited constraints on the variability of the deep‐water production in the Labrador Sea complicate reconstructions of the strength of the Atlantic Meridional Overturning Circulation (AMOC) during the Late Quaternary. Large volumes of detrital carbonates were repeatedly deposited in the Labrador Sea during the last 32 kyr, potentially affecting radiogenic Nd isotope signatures. To investigate this the Nd isotope compositions of deep and intermediate waters were extracted from the authigenic Fe‐Mn oxyhydroxide fraction, foraminiferal coatings, the residual silicates and leachates of dolostone grains. We provide a first order estimation of Nd release via dissolution of detrital carbonates and its contribution to the authigenic ԑNd signatures in the Labrador Sea. During the Last Glacial Maximum the Nd isotope signatures in the Labrador Sea would allow active water mass mixing with more radiogenic ɛNd values (−12.6 and −14) prevailing in its eastern part whereas less radiogenic values (ɛNd ∼ −18.4) were found on the western Labrador slope. The deposition of detrital carbonates during Heinrich stadials (2, 1) was accompanied by negative detrital and authigenic Nd isotope excursions (ɛNd ∼ −31) that were likely controlled by dissolution of dolostone or dolostone associated mineral inclusions. This highly unradiogenic signal dominated the authigenic phases and individual water masses in the Labrador Sea, serving as potential source of highly unradiogenic Nd to the North Atlantic region, while exported southward. The Holocene authigenic ɛNd signatures of the coatings and leachates significantly differed from those of the detrital silicates, approaching modern bottom water mass signatures during the Late Holocene. Plain Language Summary: The Labrador Sea is an important region for deep water formation and for the ocean circulation in the Atlantic region. Over the last 32 thousand years, numerous discharges from melting glaciers added freshwater to the Labrador Sea which could help understand the future effects of current melting glaciers. This information is necessary to better constrain climate predictions in order to gauge the effects on the Global Ocean Water Circulation. However, past deep water production in the Labrador is still poorly constrained, complicating reconstruction of the Atlantic Meridional Overturning Circulation on different timescales. In this study we investigated changes in deep and intermediate water mass circulation patterns over the last 32 kyr based on the radiogenic Nd isotope compositions that serve as a water mass circulation proxy. Analysis of four marine sediment cores show that the deposition of large volumes of detrital carbonates during studied period had a large effect on the recorded in the sediment column signals. New data suggest active water mass circulation during the maximum extent of glacial ice sheets. The modern day ocean circulation patterns have emerged during the Late Holocene (6 ka). Key Points: Estimation of Nd release via dissolution of detrital carbonates and its contribution to the authigenic ԑNd signatures in the Labrador Sea Dissolution of detrital dolostones in the water column during Heinrich stadials at least partially controlled ɛNd signatures During the LGM generally more radiogenic signatures possibly indicate active water mass advection and mixing in the Labrador Sea